PENGECEKAN KEASLIAN GAMBAR MENGGUNAKAN ALGORITMA KRIPTOGRAFI ADVANCED ENCRYPTION STANDARD 128 (AES), VIGENERE CIPHER DAN STEGANOGRAFI LEAST SIGNIFICANT BIT (LSB) BERBASIS ANDROID PADA CV.WIRATAMA - Diajeng Prastyanti Priyadi; Utomo Budiyanto (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2016)
An information of a digital image is stored in a metadata called EXIF. The stored information is limited and can be easily read and deleted. This would be harmful because it can be used to manipulate the report. A combination of cryptography and steganography is used in order to accommodate the information more effectively and to maintain the security and authenticity of digital data as well. The password is first encrypted using Vigenere Cipher algorithm to obtain a ciphertext. The ciphertext is then used as a secret key message in the form of a text. The text will be encrypted using AES algorithm. The encrypted text is hidden into media digital image by using LSB. The result of this research is an Android based application to validate the authenticity of an image using AES, Vigener Cipher, and LSB methods. This application can provide information geottaging as validation. The encoding process takes approximately 7.76 seconds and the decoding process takes approximately 1.77 seconds. A message inserted into the cover image can not be seen, and need to be decrypted first to read the message. Keywords: Cryptography, Advance Encryption Standard 128 (AES), Vigenere Cipher, Steganography, Least Significant Bit (LSB), Geolocation